Pengelolaan Pembiayaan Pendidikan Sekolah Dasar Negeri Poris Pelawad 5 Kota Tangerang - Haikal Adriansyah; Maftuhah Maftuhah (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2023)
This study aims to examine the management of education financing at Poris Pelawad 5 Elementary School, Tangerang City. The research method used in this study is a qualitative descriptive research method. The data collection techniques used are interviews, observations, and document studies, with research results from the principal, treasurer, and one teacher. The results showed that in the process of preparing the RKAS (Activity Plan and School Budget) was carried out by the principal and treasurer and assisted by the school management team. The management of education financing is carried out in three ways, namely, 1), planning, where activities related to schools have been prepared in the RKAS prepared by the school every year at the beginning of the school year.2), Implementation, where for the implementation of financing there are receipts such as, BOS (School Operational Assistance) of the central government, BOSDA (School Operational Assistance) of local governments, and community participation. Expenditure, referring to 8 (eight) national standards of education in schools. 3), Evaluation, this is carried out by SDN Poris Pelawad 5 Tangerang City twice every year, in the middle and at the end of the school year, by holding meetings with relevant parties. And from the results of the evaluation, it is used as a reference by the school for the future.